2003
DOI: 10.5194/hess-7-23-2003
|View full text |Cite
|
Sign up to set email alerts
|

An easily installable groundwater lysimeter to determine waterbalance components and hydraulic properties of peat soils

Abstract: A simple method for the installation of groundwater lysimeters in peat soils was developed which reduces both time and financial effort significantly. The method was applied on several sites in the Rhinluch, a fen peat land 60 km northwest of Berlin, Germany. Over a two-year period, upward capillary flow and evapotranspiration rates under grassland with different groundwater levels were measured. The installation of tensiometers and TDR probes additionally allowed the in situ determination of the soil hydrauli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 17 publications
1
31
1
Order By: Relevance
“…The water content was determined by using a site‐specific calibration between the dielectric constant, e , and the water content (standard error of calibration = 0.022 m 3 m −3 , Schwärzel and Bohl, 2003): θ=0.0393+0.0284e0.000419e2+0.00000277e3…”
Section: Methodsmentioning
confidence: 99%
“…The water content was determined by using a site‐specific calibration between the dielectric constant, e , and the water content (standard error of calibration = 0.022 m 3 m −3 , Schwärzel and Bohl, 2003): θ=0.0393+0.0284e0.000419e2+0.00000277e3…”
Section: Methodsmentioning
confidence: 99%
“…Disconnecting the capillary connection with deeper soil affects the drainage and prevents capillary rise. Several studies have shown that upward directed water fluxes from shallow groundwater tables and deeper soil layers serve as an additional water supply for evapotranspiration processes (Schwaerzel and Bohl, 2003; Yang et al, 2007; Luo and Sophocleous, 2010; Karimov et al, 2014). A seepage‐face boundary condition may lead to a bias in the drainage (Stenitzer and Fank, 2007) and in the solute transport processes (Abdou and Flury, 2004; Boesten, 2007) so that lysimeter observations are not directly transferable to field‐scale conditions (Vereecken and Dust, 1998; Flury et al, 1999).…”
mentioning
confidence: 99%
“…However, the water table is not constant but can be changed at high resolution by iteratively filling or emptying the compensation tank, which is usually done by pumping water to or from the tank while the connection between the lysimeter and tank is temporarily interrupted by closing the corresponding valve. These systems allow the groundwater level to be adjusted more flexibly, up to an intra-day basis, thus enabling a more natural groundwater behavior to be simulated (Abtew and Melesse, 2013;Bethge-Steffens et al, 2004;Meissner et al, 2008;Rupp et al, 2007;Schwaerzel and Bohl, 2003).…”
Section: Established Types Of Groundwater Lysimetersmentioning
confidence: 99%